A Review of the Protective Effects of Rosemary and its Main Ingredients Against Cancer by Modulating Nrf2 Signaling - Amiri-Ardekani, Ehsan; Radfar, Amirreza; Tavakoli-Far, Fatemeh; Farkhondeh, Tahereh; Aschner, Michael; Samini, Fariborz; Samarghandian, Saeed (Current Nutrition & Food Science, 2025)
Rosemary, as a medicinal plant, contains valuable compounds such as rosmarinic acid, rosanol, caronic acid, and carnosol. In this study, we summarized studies related to the anticancer effects of rosemary and its main ingredients by activating Nrf2. For this purpose, we searched the main databases including Scopus, PubMed, Web of Science, and MEDLINE until 2024. It was found that Rosemary and its main ingredients affect Nrf2 signaling activity, a pathway that is induced in response to oxidative stress conditions to reduce reactive oxygen species (ROS). Nrf2-related effects of Rosemary and its main ingredients have been studied in different models of diseases, including cancers. These compounds also induce apoptosis and increase antioxidant enzyme activity downstream in favor of cancer cell line death. The induction of Nrf2 activity via activating protein kinase RNA-like endoplasmic reticulum kinase results in increased phosphorylation at site threonine, downregulation of iNOS, enhancement of nerve growth factor, and activating transcription factor 4 protects cells against carcinogenesis.
Keywords: cancer